The Relationship Between Service Quality And Consumer Satisfaction At UD She Water In Gunungsitoli City - Hermanius Laia; Yupiter Mendrofa; Otanius Laia (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
The purpose of this research is to find out whether there is a relationship between service quality and consumer satisfaction and to find out how big the relationship is between service quality and consumer satisfaction at UD She Water in Gunungsitoli City. The research used in this study is quantitative research. The sample in this study was the entire population, which was 35 people. Data collection techniques. Data collection techniques used observation, questionnaires and interviews. Based on the results of the study, the researcher drew the following conclusions: 1. The implementation of proper service quality will have an impact on increasing customer satisfaction in any company including UD. She Water. 2. From the calculation of the correlation coefficient above, (rxy) item number 1 was obtained at 0.7070 and for N = 35 at a significant level of α = 5%, the data rtable = 0.334 was obtained. By referring to the valid invalid criteria, item number 1 in the questionnaire with rxy, namely 0.7070> 0.334, is concluded to be valid. 3. From the calculation of the correlation coefficient between variables X and Y, rxy = 0.7388 is obtained, then the correlation coefficient value is consulted in the r Product Moment critical value table. For N = 35 at a significance level of 5% rtable = 0.334. Thus, rxy> rtable or 0.7388> 0.334 is obtained.